Microsatellite markers for Amazon pellona Pellona castelnaeana (Clupeiformes: Pristigasteridae) - Ximenes, Aline Mourão; Hernández-Ruz, Emil José; Machado, Valéria Nogueira; Rodrigues, L. R.R.; Ritter, G. C S; Farias, Izeni P. (Genetics and Molecular Research, 2015)
The Amazon pellona is one of the few species of Pristigasteridae with recognized commercial value in the Amazon. We isolated 24 and characterized 8 microsatellite loci for this species. The number of alleles ranges from 2-8 per locus. Observed heterozygosities ranged from 0.052-0.823, while expected heterozygosities from 0.052-0.836. These 8 microsatellites are potentially valuable tools for characterizing the levels and distribution of genetic diversity, population structure, and gene flow. They may also be important parameters for the genetic conservation of this species, as well as for its sister taxon Pellona flavipinnis. © FUNPEC-RP.
Keywords: Allele; Clupeiformes; Dna Hybridization; Gene Flow; Gene Library; Gene Locus; Genetic Conservation; Genetic Parameters; Genetic Variability; Heterozygosity; Microsatellite Marker; Nonhuman; Pellona Castelnaeana; Polymerase Chain Reaction; Population Structure; Taxonomy; Animals; Classification; Environmental Protection; Fish; Gene Locus; Genetics; Heterozygote; Phylogeny; Genetics, Population; Clupeiformes; Pellona Castelnaeana; Pellona Flavipinnis; Pristigasteridae; Microsatellite Dna; Alleles; Animal; Conservation Of Natural Resources; Fishes; Gene Flow; Genetic Loci; Genetic Variation; Genetics, Population; Heterozygote; Microsatellite Repeats; Phylogeny